Effect of whey protein concentrate source on growth performance of nursery pigs - R O Gottlob; C R Neill; C W Hastad; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 228 weanling pigs (initially 14.7 lb and 21 ± 3 d of age, PIC L210 × L42) were used to evaluate the effects of whey protein concentrate (WPC) source on growth performance of weanling pigs. Pigs were fed one of seven experimental diets: a negative control, with no WPC (control); a positive control, with 5% spray-dried animal plasma (SDAP); or the negative control diet with one of five WPC sources (Sources 1 through 5). Pigs were fed the experimental diets from d 0 to 14 after weaning, then all pigs were fed a common Phase 2 diet from d 14 to 28 after weaning. From d 0 to 14, pigs fed diets containing WPC from Source 1 had greater ADG (P<0.05) than did pigs fed the control diet or WPC from Source 3. Pigs fed SDAP also had greater ADG and ADFI (P<0.05) than did pigs fed WPC from Source 3. Pigs fed WPC tended to have poorer ADFI (P<0.09) than that of pigs fed SDAP. All pigs fed WPC diets had improved F/G (P<0.01), however, compared with pigs fed the control. Overall (d 0 to 28), pigs fed WPC from Source 1 had greater ADG (P<0.05) than did pigs fed WPC from Source 3, but there were no treatment differences in ADFI and F/G. In summary, variation in growth performance with pigs fed WPC confirms our previous results in that variation between sources does exist. Furthermore, pigs fed diets containing high-quality WPC, from a reliable and consistent source, can improve ADG and have similar performance to pigs fed spray-dried animal plasma.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine Research; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Nursery pig; Spray-dried animal plasma; Whey protein concentrate; Swine